2021
DOI: 10.52403/ijhsr.20210429
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Peak Expiratory Flow Rate between Android and Gynoid Pattern Obesity in Females

Abstract: Aim: To assess comparison of PEFR between Android and Gynoid Pattern Obesity in Females. Objectives: To assess Peak Expiratory Flow Rate in Android Pattern, Gynoid Pattern of Obesity in Females and compare Peak Expiratory Flow Rate between Android and Gynoid Pattern Obesity in Females. Methodology: 100 Female Obese Subjects with BMI> 30 in the Age Group between 20-40 yrs living a sedentary lifestyle were recruited with incidental sampling over the period of 1 year duration and allocated to Android (n = 50) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The research answered that there is a reduction in post-operative depressive function among CABG patients. 17 In line with the results, we found that the anxiety symptoms are improved within the Nadi-shodhana pranayama group. Thapa S et al in their single-center prospective study, found out that chair aerobics has a positive role in vital signs among post-CABG patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The research answered that there is a reduction in post-operative depressive function among CABG patients. 17 In line with the results, we found that the anxiety symptoms are improved within the Nadi-shodhana pranayama group. Thapa S et al in their single-center prospective study, found out that chair aerobics has a positive role in vital signs among post-CABG patients.…”
Section: Discussionsupporting
confidence: 87%
“…16 Routine care is not withheld in both groups. 17,18 The tool" hospital anxiety and depression scale" measured anxiety. Heart rate is estimated to know the somatic and physiologic components of anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Excess adipose tissue contributes to the cardiovascular and other risks associated with being obese. (2) Adiposity markers like Body Mass Index, Waist Circumference, Waist Hip Ratio, and Hip Circumference help in better prediction of Body Fat between Android and Gynoid Pattern (3) The World Health Organization (WHO) adopted body mass index (BMI), which is calculated by Dividing the body weight in kilograms (Kg) by the square of the height in metres (m), as a surrogate Measure of total body fat. Body Mass Index is the most Volume 8; Issue: 3; July-September 2023 commonly used parameter to determine obesity (4) The GE Healthcare systems define the android region as the area between the ribs and the pelvis that is totally enclosed by the trunk region.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The aim of this study is to determine the effect of cotton dust on PEFR and chest expansion among cotton textile workers. [8] : Peak expiratory flow rate was measured using mini wright peak flow meter. Subjects were instructed to take a deep breath and exhale as possible in one single blow into the instrument.…”
Section: Introductionmentioning
confidence: 99%